Mechanoluminescence composite material and preparation method and application thereof

By modifying metal fluoride in aluminum acid and mixed with rare earth ions, heterogeneous knots are formed to solve the problem of weak brightness and poor duplication of light -emitting materials, and realize high brightness and high repetitive force. Essence

CN119331608APending Publication Date: 2025-01-21LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411448346.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing electroluminescent materials have problems of weak brightness and poor repeatability, which limits their use in practical applications.

Method used

By modifying metal fluoride into aluminum acid, and mixed with rare earth and doped, heterogeneous knots are formed, thereby improving the luminous strength and repetitiveness of the material.

Benefits of technology

The high brightness and high repeatability of the electroluminescent composite material were achieved, improving its performance in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331608A_ABST
    Figure CN119331608A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic luminescent materials, in particular to a mechanoluminescent composite material and a preparation method thereof. The invention provides a mechanoluminescence composite material. The mechanoluminescence composite material comprises aluminate modified by metal fluoride and rare earth doped ions doped in the aluminate modified by the fluoride, the metal fluoride modified aluminate comprises aluminate and metal fluoride, and a heterojunction is formed between the aluminate and the metal fluoride. The mechanoluminescence composite material has high crystallinity and high purity, and also has mechanoluminescence properties of high brightness and high repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mechanoluminescent materials, and in particular to a mechanoluminescent composite material and a preparation method and application thereof. Background Art

[0002] In recent years, mechanoluminescent materials have shown broad application prospects in stress sensing and monitoring, green lighting, biomedicine, information encryption, anti-counterfeiting, structural health monitoring and electronic skin because they can achieve direct conversion of mechanical and optical signals without additional circuit design. With people's emphasis and attention on energy conservation, the research on mechanoluminescent materials has attracted more and more attention from peers. At present, most mechanoluminescent materials are mostly concentrated in trap-type structures, which have the disadvantages of low shell, low repeatability and lack of self-recovery and cannot be reused, which seriously limits the application of mechanoluminescent materials in more real life. Therefore, it is crucial to develop high-performance mechanoluminescent materials, and how to improve the performance of trap-type mechanoluminescent materials has become a key research topic.

[0003] At present, in the research of mechanoluminescent materials, traditional mechanoluminescent materials such as aluminates and silicates have problems such as poor reproducibility, which seriously limits their practical application. Although fluoride-based mechanoluminescent materials have good reproducibility, their brightness is weak and it is difficult to meet the actual application needs. Summary of the invention

[0004] The object of the present invention is to provide a mechanoluminescent composite material and a preparation method and application thereof, wherein the mechanoluminescent composite material has both high brightness and high repeatability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a mechanoluminescent composite material, which comprises a metal fluoride-modified aluminate and rare earth doping ions doped in the fluoride-modified aluminate;

[0007] The metal fluoride-modified aluminate comprises aluminate and metal fluoride, and a heterojunction is formed between the aluminate and the metal fluoride.

[0008] Preferably, the metal fluoride in the metal fluoride-modified aluminate is one or more of NaF, CaF2, MgF2, AlF3 and SrF2.

[0009] Preferably, the aluminate in the metal fluoride modified aluminate is M'Al2O4, SrAl4O7, Sr4Al 14 O 25 、CaAl4O7、CaAl8O 13 , CaAl12 O 19 and Ca 12 Al 14 O 33 One or more of the following;

[0010] The M' in the M'Al2O4 is one or more of Sr, Ca, Ba and Mg.

[0011] Preferably, the rare earth doping ion is Ce 4+ , Pr 3+ 、Eu 2+ 、Eu 3+ 、Dy 3+ , Tb 3+ 、Ho 3+ 、Sm 2+ and Tm 3+ One or more of the .

[0012] Preferably, the molar ratio of the metal fluoride-modified aluminate to the rare earth doping ions in the mesoluminescent composite material is 1:(0.01-0.1).

[0013] The present invention also provides a method for preparing the mechanoluminescent composite material described in the above technical solution, comprising the following steps:

[0014] Mixing metal fluoride, Al2O3 and rare earth oxide, and sintering to obtain the mesoluminescent composite material;

[0015] The metal in the metal fluoride is the metal in the metal fluoride in the metal fluoride-modified aluminate and the metal in the aluminate.

[0016] Preferably, the sintering temperature is 1100-1600° C. and the sintering time is 2-5 hours.

[0017] The present invention also provides a method for preparing the mechanoluminescent composite material described in the above technical solution, comprising the following steps:

[0018] Metal carbonate, Al2O3 and rare earth oxide are mixed and first sintered to obtain MAl x O y : Ln aluminate precursor, the metal in the metal carbonate is the same as the metal in the aluminate;

[0019] The MA1 x O y : a Ln aluminate precursor and a metal fluoride are mixed and subjected to a second sintering to obtain the mesoluminescent composite material, wherein the metal in the metal fluoride is the same as the metal in the metal fluoride in the metal fluoride-modified aluminate;

[0020] The MA1 x O y : In the Ln aluminate precursor, M is the same type as the metal in the metal carbonate, Ln is the same type as the rare earth element in the rare earth oxide, the value range of x is 1-14, and the value range of y is 4-33.

[0021] Preferably, the first sintering temperature is 1200-1700°C and the time is 2-5h;

[0022] The second sintering temperature is 1100-1600° C., and the time is 2-5 hours.

[0023] The present invention also provides the use of the mechanoluminescent composite material described in the above technical solution or the mechanoluminescent composite material prepared by the preparation method described in the above technical solution in a mechanoluminescent composite elastomer.

[0024] The present invention provides a mechanoluminescent composite material, the mechanoluminescent composite material comprises aluminate modified by metal fluoride and rare earth doping ions doped in the aluminate modified by fluoride; the aluminate modified by metal fluoride comprises aluminate and metal fluoride, and a heterojunction is formed between the aluminate and the metal fluoride. In the mechanoluminescent composite material of the present invention, a heterojunction interface is formed between the metal fluoride and the aluminate, and the heterojunction interface can effectively promote the transfer and combination of charges by regulating carrier transport through energy band, thereby improving its luminescence intensity and carrier transport efficiency, that is, the mechanoluminescence performance is significantly improved. And because the physical and chemical properties of the regular morphology mechanoluminescent composite material are more stable, the metal fluoride can reduce the sintering temperature; it can also improve the amorphous morphology of the mechanoluminescent composite material, reduce the local stress concentration caused by the irregular morphology or the factors that are easily affected by the external environment, thereby improving the stability of the luminescence performance; it can also make the crystal structure of the mechanoluminescent composite material more complete, reduce crystal defects, and reduce the probability of non-radiative transition of the luminescence center, thereby enhancing the luminescence intensity. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The X-ray diffraction spectra of the mechanoluminescent composite materials prepared in Examples 1 to 4;

[0026] Figure 2 The crystal surface structure morphology of the mechanoluminescent composite material prepared in Examples 1 to 4 measured on a scanning electron microscope;

[0027] Figure 3 The mechanoluminescence spectra of the mechanoluminescence composite elastomers described in Comparative Examples 1 to 6 under the same stretching conditions;

[0028] Figure 4 The mechanoluminescence spectra of the mechanoluminescence composite elastomers described in Examples 1 to 4 and the mechanoluminescence composite elastomer described in Comparative Example 1 under the same stretching conditions;

[0029] Figure 5 It is a scatter plot of the mechanoluminescence repeatability of the mechanoluminescence composite elastomers described in Examples 1 to 4 and Comparative Examples 1 to 3 under the same stretching conditions;

[0030] Figure 6 XRD diagrams of the mechanoluminescent composite materials described in Examples 5 to 16 and Comparative Examples 4 to 7;

[0031] Figure 7 The SEM images of the mechanoluminescent composite materials described in Examples 5 to 7 and Comparative Example 1;

[0032] Figure 8 are SEM images of the mechanoluminescent composite materials described in Examples 7 to 10;

[0033] Fig. 9 The mechanoluminescence spectra of the mechanoluminescence composite elastomers described in Examples 5 to 7 and Comparative Example 1 under the same stretching conditions;

[0034] Fig.10 It is a scatter plot of the repeatability of the mechanoluminescence of the mechanoluminescence composite elastomer described in Examples 7 to 10 under the same stretching conditions. DETAILED DESCRIPTION

[0035] The present invention provides a mechanoluminescent composite material, which comprises a metal fluoride-modified aluminate and rare earth doping ions doped in the fluoride-modified aluminate;

[0036] The metal fluoride-modified aluminate comprises aluminate and metal fluoride, and a heterojunction is formed between the aluminate and the metal fluoride.

[0037] In the present invention, the metal fluoride in the metal fluoride-modified aluminate is preferably one or more of NaF, CaF2, MgF2, AlF3 and SrF2. When the metal fluoride is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the fluoride is specifically CaF2.

[0038] In the present invention, the aluminate in the metal fluoride modified aluminate is M'Al2O4, SrAl4O7, Sr4Al 14 O 25 、CaAl4O7、CaAl8O 13 , CaAl 12 O 19 and Ca12 Al 14 O 33 In the embodiment of the present invention, the aluminate is specifically CaAl2O4 (CA), CaAl4O7 (CA2), CaAl8O 13 (CA4) or CaAl 12 O 19 (CA6).

[0039] In the present invention, the rare earth doping ions are preferably Ce 4+ , Pr 3+ 、Eu 2+ 、Eu 3+ 、Dy 3+ , Tb 3+ 、Ho 3+ 、Sm 2+ and Tm 3+ When the rare earth doping ion is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the embodiment of the present invention, the rare earth doping ion is specifically Dy 3+ .

[0040] In the present invention, the molar ratio of the metal fluoride-modified aluminate and the rare earth doping ion in the mechanoluminescent composite material is preferably 1:(0.01-0.1), and more preferably 1:(0.03-0.06). The present invention does not specifically limit the amount of metal fluoride modification in the metal fluoride-modified aluminate, and the modification amount familiar to those skilled in the art can be used. In an embodiment of the present invention, the mass ratio of the metal fluoride and the aluminate in the metal fluoride-modified aluminate can be 1:1, 3:1, or 6:1; the metal fluoride can be calcium fluoride; the rare earth doping ion can be Dy 3+ In an embodiment of the present invention, the mechanoluminescent composite material may be CaF2 / CA6:Dy 3+ (CaF2 / CA6 and Dy 3+ The molar ratio is 1:0.04).

[0041] The method for preparing the mechanoluminescent composite material of the present invention comprises the following steps:

[0042] Mixing metal fluoride, Al2O3 and rare earth oxide, and sintering to obtain the mesoluminescent composite material;

[0043] The metal in the metal fluoride is the metal in the metal fluoride and the metal in the aluminate in the metal fluoride-modified aluminate.

[0044] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0045] In the present invention, the purity of the metal fluoride, Al2O3 and rare earth oxide is preferably ≥99.9%.

[0046] In the present invention, the mixing is preferably carried out under grinding conditions. The present invention does not have any special limitation on the grinding process, and the grinding process may be carried out using a process well known to those skilled in the art.

[0047] In the present invention, the sintering temperature is preferably 1100-1600°C, more preferably 1200-1500°C, and most preferably 1300-1400°C; the sintering time is preferably 2-5h, more preferably 2.5-4.5h, and most preferably 3-4h. In an embodiment of the present invention, the sintering temperature is specifically 1300°C, and the sintering time is specifically 4h.

[0048] After the sintering is completed, the present invention also preferably includes cooling and grinding performed in sequence. The present invention has no special limitation on the cooling and grinding process, and the process well known to those skilled in the art can be used.

[0049] The present invention also provides a method for preparing the mechanoluminescent composite material described in the above technical solution, comprising the following steps:

[0050] Metal carbonate, Al2O3 and rare earth oxide are mixed and first sintered to obtain MAl x O y : Ln aluminate precursor, the metal in the metal carbonate is the same as the metal in the aluminate;

[0051] The MA1 x O y : a Ln aluminate precursor and a metal fluoride are mixed and subjected to a second sintering to obtain the mesoluminescent composite material, wherein the metal in the metal fluoride is the same as the metal in the metal fluoride in the metal fluoride-modified aluminate;

[0052] The MA1 x O y : In the Ln aluminate precursor, M is the same type as the metal in the metal carbonate, Ln is the same type as the rare earth element in the rare earth oxide, the value range of x is 1-14, and the value range of y is 4-33.

[0053] The present invention mixes metal carbonate, Al2O3 and rare earth oxide, and performs a first sintering to obtain MAl x O y : Ln aluminate precursor, the metal in the metal carbonate is the same as the metal in the aluminate; the MAl x O y : In the Ln aluminate precursor, M is the same type as the metal in the metal carbonate, Ln is the same type as the rare earth element in the rare earth oxide, the value range of x is 1-14, and the value range of y is 4-33.

[0054] In the present invention, the metal carbonate is preferably analytically pure. The purity of the Al2O3 and rare earth oxide is preferably ≥ 99.9%.

[0055] In the present invention, the mixing is preferably carried out in a dispersion medium, and the dispersion medium is preferably alcohol. The present invention does not have any special restrictions on the amount of the alcohol, and the amount well known to those skilled in the art can be used. In the present invention, the mixing method is preferably grinding, and the present invention does not have any special restrictions on the grinding process, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the grinding is carried out in an agate mortar.

[0056] The mixing may also include drying. The present invention does not have any particular limitation on the drying process, and the drying process may be carried out using a process well known to those skilled in the art.

[0057] In the present invention, the atmosphere of the first sintering is preferably air. The temperature of the first sintering is preferably 1200-1700°C, more preferably 1300-1600°C, and most preferably 1400-1500°C; the time is preferably 2-5h, more preferably 2.5-4.5h, and most preferably 3-4h. In an embodiment of the present invention, the temperature of the first sintering is specifically 1600°C and 1400°C, and the time is specifically 4h. In the present invention, the process of the first sintering is specifically to place the mixed mixture in an alumina crucible and carry out the sintering in a box furnace.

[0058] After the first sintering is completed, the present invention preferably further comprises cooling and grinding performed in sequence. The present invention has no special limitation on the cooling and grinding process, and the cooling and grinding process may be performed using a process well known to those skilled in the art.

[0059] Get MAl x O y : Ln aluminate precursor, the present invention is said MAl x O y: A Ln aluminate precursor and a metal fluoride are mixed and subjected to a second sintering to obtain the mesoluminescent composite material, wherein the metal in the metal fluoride is the same as the metal in the metal fluoride in the metal fluoride-modified aluminate.

[0060] In the present invention, the mixing method is preferably grinding. The present invention has no special limitation on the grinding process, and the grinding process can be carried out using a process well known to those skilled in the art.

[0061] In the present invention, the atmosphere of the second sintering is preferably air. In the present invention, the temperature of the second sintering is preferably 1100-1600°C, more preferably 1200-1500°C, and most preferably 1300-1400°C; the time is preferably 2-5h, more preferably 2.5-4.5h, and most preferably 3-4h. In an embodiment of the present invention, the temperature of the second sintering is specifically 1400°C, 1300°C, and the time is specifically 4h. In the present invention, the second sintering is preferably carried out in a box-type electric furnace.

[0062] After the second sintering is completed, the present invention preferably further comprises cooling and grinding performed in sequence. The present invention has no special limitation on the cooling and grinding process, and the cooling and grinding process may be performed using a process well known to those skilled in the art.

[0063] The present invention also provides the use of the mechanoluminescent composite material described in the above technical solution or the mechanoluminescent composite material prepared by the preparation method described in the above technical solution in a mechanoluminescent composite elastomer.

[0064] In the present invention, the method for preparing the force-induced composite elastomer preferably comprises the following steps:

[0065] Mixing a prepolymer, a curing agent and the mechanoluminescent composite material described in the above technical solution to obtain a mixture;

[0066] The mixture is cured to obtain the mechanically induced composite elastomer.

[0067] The present invention mixes the prepolymer, the curing agent and the mechanoluminescent composite material described in the above technical solution to obtain a mixture.

[0068] In the present invention, the prepolymer is preferably a commercial transparent substrate; the commercial transparent substrate is preferably polydimethylsiloxane (PDMS), silica gel (SG), polyurethane (PU) or epoxy resin (ER).

[0069] In the present invention, the mass ratio of the prepolymer to the curing agent is preferably (1-10): (0.5-3), and more preferably (1-10): (0.7-1.5). In the present invention, the prepolymer and the curing agent are both commercially available matching products.

[0070] In the present invention, the ratio of the total mass of the prepolymer and the curing agent to the mass of the force-induced luminescent composite material is preferably 1:(0.5-2), and more preferably 1:(1-1.5).

[0071] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention has no special limitation on the stirring process, and the stirring process can be carried out by a process well known to those skilled in the art. The mixing is preferably carried out by mixing the prepolymer and the curing agent, and then adding the mechanoluminescent composite material.

[0072] After obtaining the mixture, the present invention solidifies the mixture to obtain the force-induced composite elastomer.

[0073] Before the curing, the mixture is preferably degassed in the present invention. The degassing temperature is preferably <30° C., the vacuum degree is preferably 0.015 to 0.03 MPa, and the degassing time is preferably 5 to 10 min.

[0074] The present invention does not have any special limitation on the curing process, and the curing process may be carried out using a process well known to those skilled in the art.

[0075] The following is a detailed description of the power-induced luminescent composite material provided by the present invention, its preparation method and application in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0076] Example 1

[0077] According to CaF2 / CA:Dy 0.04 CaF2(AR), Al2O3(AR) (the molar ratio of CaF2 to Al2O3 is 1:1) and Dy2O3 (99.99%) were weighed and mixed. The mixture was fully ground in an agate mortar, dried and transferred to an alumina crucible, placed in a box furnace, heated to 1300°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4h, cooled to room temperature, and ground into powder to obtain a mechanoluminescent composite material (CaF2 / CA:Dy 0.04 );

[0078] Polydimethylsiloxane (PDMS) and a curing agent are uniformly mixed in a mass ratio of 10:1 to obtain a prepolymer;

[0079] According to the mass ratio of 1:2, the CaF2 / CA:Dy 0.04 The mechanoluminescent composite material was added to the prepolymer, stirred until uniform, transferred to a mold, placed in a vacuum oven (room temperature, 20 kPa) for degassing for 10 minutes, and cured at 70° C. for 40 minutes to obtain a mechanoluminescent composite elastomer.

[0080] Example 2

[0081] According to CaF2 / CA2:Dy 0.04 CaF2(AR), Al2O3(AR) (the molar ratio of CaF2 to Al2O3 is 1:2) and Dy2O3 (99.99%) were weighed and mixed. The mixture was fully ground in an agate mortar, dried and transferred to an alumina crucible, placed in a box furnace, heated to 1300°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4h, cooled to room temperature, and ground into powder to obtain a mechanoluminescent composite material (CaF2 / CA2:Dy 0.04 );

[0082] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0083] Example 3

[0084] According to CaF2 / CA4:Dy 0.04 CaF2(AR), Al2O3(AR) (the mass ratio of CaF2 to Al2O3 is 1:4) and Dy2O3 (99.99%) were weighed and mixed. The mixture was fully ground in an agate mortar, dried and transferred to an alumina crucible, placed in a box furnace, heated to 1300°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4h, cooled to room temperature, and ground into powder to obtain a mechanoluminescent composite material (CaF2 / CA4:Dy 0.04 );

[0085] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0086] Example 4

[0087] According to CaF2 / CA6:Dy 0.04 CaF2(AR), Al2O3(AR) (the mass ratio of CaF2 to Al2O3 is 1:6) and Dy2O3 (99.99%) were weighed and mixed. The mixture was fully ground in an agate mortar, dried and transferred to an alumina crucible, placed in a box furnace, heated to 1300°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4h, cooled to room temperature, and ground into powder to obtain a mechanoluminescent composite material (CaF2 / CA6:Dy 0.04 );

[0088] The preparation method of the force-induced composite elastomer is as described in Example 1, and the force-induced composite elastomer is obtained;

[0089] Figure 1is the X-ray diffraction spectrum of the mechanoluminescent composite material prepared in Examples 1 to 4, Figure 1 It can be seen that all diffraction peaks of the mechanoluminescent composite materials prepared in Examples 1 to 4 are consistent with the standard inorganic crystal structure databases JCPDS#35-0816CaF2 and JCPDS#38-0470CA6, and trace amounts of Al2O3 do not affect the host lattice changes, indicating that the mechanoluminescent composite materials are successfully prepared and that the doping of Dy2O3 does not produce any impurities;

[0090] Figure 2 The crystal surface structure morphology of the mechanoluminescent composite material prepared in Examples 1 to 4 was measured on a scanning electron microscope. Figure 2 It can be seen that the mechanoluminescent composite material has a morphology of several tens of microns in size and a complete crystal form. And as the ratio of CaF2 and Al2O3 increases, the material morphology gradually changes from hexagonal to uniform spherical. Therefore, by in-situ sintering of Examples 1 to 4 to composite calcium fluoride with aluminate materials, a mechanoluminescent composite elastomer with high crystallinity can be synthesized.

[0091] Example 5

[0092] According to CA6:Dy 0.04 The stoichiometric ratio of CaCO3 (AR), Al2O3 (AR) and Dy2O3 (99.99%) was weighed and mixed in an agate mortar and ground thoroughly. After drying, the mixture was transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1600°C at a rate of 5°C / min and sintered for 4 h. After cooling, the mixture was ground into powder to obtain a mechanoluminescent composite material (CA6:Dy 0.04 );

[0093] Calcium fluoride and CA6:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1400°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (CaF2@CA6:Dy 0.04 , the mass ratio of CaF2 and CA6 is 1:1);

[0094] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0095] Example 6

[0096] Reference Example 5, the difference is that: calcium fluoride and CA6:Dy 0.04The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1400°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (3CaF2@CA6:Dy 0.04 , the mass ratio of CaF2 and CA6 is 3:1);

[0097] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0098] Example 7

[0099] Reference Example 5, the difference is that: calcium fluoride and CA6:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1400°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (6CaF2@CA6:Dy 0.04 , the mass ratio of CaF2 and CA6 is 6:1);

[0100] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0101] Example 8

[0102] According to CA:Dy 0.04 The stoichiometric ratio of CaCO3 (AR), Al2O3 (AR) and Dy2O3 (99.99%) was weighed and mixed in an agate mortar and ground thoroughly. After drying, the mixture was transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1400°C at a rate of 5°C / min and sintered for 4h. After cooling, the mixture was ground into powder to obtain a mechanoluminescent composite material (CA:Dy 0.04 );

[0103] Calcium fluoride and CA:Dy 0.04 The mixture was ground and mixed, and then placed in a box-type electric furnace and heated to 1300°C at a heating rate of 5°C / min for a second sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (6CaF2@CA:Dy 0.04 , the mass ratio of CaF2 and CA is 6:1);

[0104] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0105] Example 9

[0106] According to CA2:Dy 0.04The stoichiometric ratio of CaCO3 (AR), Al2O3 (AR) and Dy2O3 (99.99%) was weighed and mixed in an agate mortar and ground thoroughly. After drying, the mixture was transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1400°C at a rate of 5°C / min and sintered for 4h. After cooling, the mixture was ground into powder to obtain a mechanoluminescent composite material (CA2:Dy 0.04 );

[0107] Calcium fluoride and CA2:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (6CaF2@CA2:Dy 0.04 , the mass ratio of CaF2 and CA2 is 6:1);

[0108] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0109] Example 10

[0110] According to CA4:Dy 0.04 CaCO3(AR), Al2O3(AR) and Dy2O3(99.99%) were weighed and mixed in an agate mortar and ground thoroughly. After drying, they were transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1400℃ at a rate of 5℃ / min and sintered for 4h. After cooling, they were ground into powder to obtain CA4:Dy 0.04 ;

[0111] Calcium fluoride and CA4:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (6CaF2@CA4:Dy 0.04 , the mass ratio of CaF2 and CA4 is 6:1);

[0112] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0113] Embodiment 11

[0114] Reference Example 8, the difference is that calcium fluoride and CA:Dy are mixed in a mass ratio of 1:1. 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (CaF2@CA:Dy 0.04, the mass ratio of CaF2 and CA is 1:1);

[0115] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0116] Example 12

[0117] Reference Example 8, the difference is that calcium fluoride and CA:Dy are mixed in a mass ratio of 3:1. 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (3CaF2@CA:Dy 0.04 )(The mass ratio of CaF2 and CA is 3:1);

[0118] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0119] Embodiment 13

[0120] Reference Example 9, the difference is that calcium fluoride and CA2:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (CaF2@CA2:Dy 0.04 , the mass ratio of CaF2 and CA2 is 1:1);

[0121] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0122] Embodiment 14

[0123] Reference Example 9, the difference is that calcium fluoride and CA2:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (3CaF2@CA2:Dy 0.04 , the mass ratio of CaF2 and CA2 is 3:1);

[0124] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0125] Embodiment 15

[0126] Reference Example 10, except that calcium fluoride and CA4:Dy 0.04The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (CaF2@CA4:Dy 0.04 , the mass ratio of CaF2 and CA4 is 1:1);

[0127] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0128] Example 16

[0129] Reference Example 10, except that calcium fluoride and CA4:Dy 0.04 The mixture was ground and placed in a box-type electric furnace at a heating rate of 5°C / min to 1300°C for secondary sintering in air for 4 h. After cooling to room temperature, the mixture was ground into powder again to obtain a mechanoluminescent composite material (3CaF2@CA4:Dy 0.04 , the mass ratio of CaF2 and CA4 is 3:1);

[0130] The preparation method of the force-induced composite elastomer is similar to that of Example 1 to obtain the force-induced composite elastomer.

[0131] Comparative Example 1

[0132] According to CA6:Dy 0.04 CaCO3(AR), Al2O3(AR) and Dy2O3(99.99%) were weighed and mixed in an agate mortar and ground thoroughly. After drying, they were transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1600℃ at a rate of 5℃ / min and sintered for 4h. After cooling, they were ground into powder to obtain CA6:Dy 0.04 ;

[0133] The CA6:Dy 0.04 Add the prepolymer, stir until uniform, transfer to a mold, place in a vacuum oven (room temperature, 20 kPa) for degassing for 10 min, and cure at 70 ° C for 40 min to obtain a force-induced composite elastomer (CA6:Dy 0.04 / PDMS);

[0134] Figure 4 The force-induced light emission spectra of the force-induced composite elastomers described in Examples 1 to 4 and the force-induced composite elastomer described in Comparative Example 1 under the same stretching conditions (the conditions of the stretching test are: stretching rate 3 Hz, stretching frequency 60%) are shown in FIG. Figure 4It can be seen that the mechanoluminescence intensity of the mechanoluminescence composite elastomers described in Examples 1 to 4 at a wavelength of 580 nm is significantly higher than that of the mechanoluminescence composite elastomer described in Comparative Example 1, and as the molar ratio of Al2O3 to CaF2 increases, the mechanoluminescence intensity of the material gradually increases. When the molar ratio of Al2O3 to CaF2 is 6:1, the formed CaF2 / CA6:Dy 0.04 The best mesoluminescence intensity indicates that CaF2 / CaAl based on calcium fluoride x O y :Dy 0.04 The mesoluminescence intensity of / PDMS composite elastomer is better than that of CaAl x O y :Dy 0.04 / PDMS, CaF2:Dy 0.04 / PDMS or physically mixed CaAl x O y :Dy 0.04 +CaF2:Dy 0.04 Therefore, using calcium fluoride as a raw material to modify aluminate can form a high-brightness mechanoluminescent composite material.

[0135] Comparative Example 2

[0136] According to CaF2:Dy 0.04 CaF2(AR) and Dy2O3(99.99%) were weighed and mixed in a stoichiometric ratio. The mixture was fully ground in an agate mortar, dried, transferred to an alumina crucible, placed in a box furnace, heated to 1400°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4h, cooled to room temperature, and ground into powder to obtain CaF2:Dy 0.04 ;

[0137] Polydimethylsiloxane (PDMS) and a curing agent (PDMS) were uniformly mixed in a mass ratio of 10:1 to obtain a prepolymer;

[0138] The CaF2:Dy 0.04 Add the prepolymer, stir until uniform, transfer to a mold, place in a vacuum oven (room temperature, 20 kPa) for degassing for 10 min, and cure at 70 ° C for 40 min to obtain a force-induced composite elastomer (CaF2: Dy 0.04 / PDMS).

[0139] Comparative Example 3

[0140] According to CA6:Dy 0.04CaCO3(AR), Al2O3(AR) and Dy2O3(99.99%) were weighed and mixed in an agate mortar and ground thoroughly. After drying, they were transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1600℃ at a rate of 5℃ / min and sintered for 4h. After cooling, they were ground into powder to obtain CA6:Dy 0.04 ;

[0141] According to CaF2:Dy 0.04 CaF2(AR) and Dy2O3(99.99%) were weighed and mixed in a stoichiometric ratio. The mixture was fully ground in an agate mortar, dried, transferred to an alumina crucible, placed in a box furnace, heated to 1400°C at a heating rate of 5°C / min in an air atmosphere, sintered for 4h, cooled to room temperature, and ground into powder to obtain CaF2:Dy 0.04 ;

[0142] According to the mass ratio of 1:1, CA6:Dy 0.04 and CaF2:Dy 0.04 After mixing, the obtained mixture was mixed with the prepolymer in a mass ratio of 1:2 to obtain a force-induced composite elastomer (CaF2:Dy 0.04 +CA6:Dy 0.04 / PDMS).

[0143] Comparative Example 4

[0144] According to CA:Dy 0.04 CaCO3(AR), Al2O3(AR) and Dy2O3(99.99%) were weighed and mixed in an agate mortar and ground thoroughly. After drying, they were transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1600℃ at a rate of 5℃ / min and sintered for 4h. After cooling, they were ground into powder to obtain CA:Dy 0.04 ;

[0145] According to the mass ratio of 1:2, the CA:Dy 0.04 Add the prepolymer, stir until uniform, transfer to a mold, place in a vacuum oven (room temperature, 20 kPa) for degassing for 10 min, and cure at 70 ° C for 40 min to obtain a force-induced composite elastomer (CA: Dy 0.04 / PDMS).

[0146] Comparative Example 5

[0147] According to CA2:Dy 0.04CaCO3(AR), Al2O3(AR) and Dy2O3 (99.99%) were weighed and mixed in an agate mortar and ground thoroughly. After drying, they were transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1600°C at a rate of 5°C / min and sintered for 4 h. After cooling, they were ground into powder to obtain CA2:Dy 0.04 ;

[0148] The CA2:Dy 0.04 Add the prepolymer, stir until uniform, transfer to a mold, place in a vacuum oven (room temperature, 20 kPa) for degassing for 10 min, and cure at 70 ° C for 40 min to obtain a force-induced composite elastomer (CA2:Dy 0.04 / PDMS).

[0149] Comparative Example 6

[0150] According to CA4:Dy 0.04 CaCO3(AR), Al2O3(AR) and Dy2O3(99.99%) were weighed and mixed in an agate mortar and ground thoroughly. After drying, they were transferred to an alumina crucible and placed in a box furnace. The temperature was raised to 1600℃ at a rate of 5℃ / min and sintered for 4h. After cooling, they were ground into powder to obtain CA4:Dy 0.04 ;

[0151] The CA4:Dy 0.04 Add the prepolymer, stir until uniform, transfer to a mold, place in a vacuum oven (room temperature, 20 kPa) for degassing for 10 min, and cure at 70 ° C for 40 min to obtain a force-induced composite elastomer (CA4:Dy 0.04 / PDMS).

[0152] Figure 3 The force-induced light emission spectra of the force-induced composite elastomers described in Comparative Examples 1 to 6 under the same stretching conditions (stretching conditions: stretching rate 3 Hz, stretching frequency 60%) are shown in FIG. Figure 3 It can be seen that the force-induced composite elastomer described in Comparative Example 1 exhibits the best force-induced luminescence intensity. Therefore, the ML intensity of the force-induced composite elastomer described in the present invention only needs to be compared with that of Comparative Example 1.

[0153] Figure 5 The scatter diagram of the repeatability of the mechanoluminescence of the mechanoluminescence composite elastomers described in Examples 1 to 4 and Comparative Examples 1 to 3 under the same stretching conditions is shown in FIG. Figure 5It can be seen that the repeatability of the force-induced composite elastomers described in Examples 1 to 4 is significantly better than that of the force-induced composite elastomers described in Comparative Examples 1 to 3, and as the ratio of aluminum oxide to calcium fluoride increases, the repeatability of the force-induced composite elastomer becomes stronger; the repeatability of the force-induced composite elastomer described in Example 4 is about 1800 times, which is 100 times that of the force-induced composite elastomer described in Comparative Example 1, 12 times that of the force-induced composite elastomer described in Comparative Example 2, and 13 times that of the force-induced composite elastomer described in Comparative Example 3, indicating that calcium fluoride and aluminate can be combined to synthesize a highly repeatable composite mechanoluminescent material;

[0154] Figure 6 The XRD diagrams of the mechanoluminescent composite materials described in Examples 5 to 16 and Comparative Examples 4 to 7 are shown in FIG. Figure 6 It can be seen that all the diffraction peaks of the mechanoluminescent composite materials described in Examples 8 to 16 are consistent with the standard inorganic crystal structure databases CaF2 (JCPDS#35-0816), aluminate CaAl2O4 (JCPDS#70-0134), CaAl4O7 (JCPDS#23-1037) and CaAl 12 O 19 (JCPDS#38-0470), indicating that the mechanoluminescent composite material was successfully prepared and that the doping of Dy2O3 did not produce any impurities;

[0155] Figure 7 The SEM images of the mechanoluminescent composite materials described in Examples 5 to 7 and Comparative Example 1 are shown in FIG. Figure 7 It can be seen that the mechanoluminescent composite materials described in Examples 5 to 7 have a morphology of several tens of microns in size and a complete crystal shape. 0.04 As the ratio increases, the sample size of the material at the same scanning magnification gradually increases. Therefore, Examples 5 to 7 successfully prepared highly crystalline mesoluminescent composite materials;

[0156] Figure 8 The SEM images of the mechanoluminescent composite materials described in Examples 7 to 10 are shown in FIG. Figure 8 It can be seen that the mechanoluminescent composite materials described in Examples 7 to 10 have a morphology of several tens of microns in size and a complete crystal shape. Examples 7 to 10 successfully prepared highly crystalline mechanoluminescent composite materials;

[0157] Fig. 9 The force-induced light emission spectra of the force-induced composite elastomers described in Examples 5 to 7 and Comparative Example 1 under the same stretching conditions (stretching conditions: stretching rate 3 Hz, stretching frequency 60%) are shown in FIG. Fig. 9It can be seen that the mechanoluminescence intensity of the mechanoluminescence composite elastomers described in Examples 5 to 7 at a wavelength of 580 nm is significantly higher than that of the mechanoluminescence composite elastomer described in Comparative Example 1, indicating that the mechanoluminescence intensity of the mechanoluminescence composite elastomer based on calcium fluoride is better than that of CaAl x O y :Dy 0.04 / PDMS, CaF2:Dy 0.04 / PDMS or physically mixed CaAl x O y :Dy 0.04 +CaF2:Dy 0.04 / PDMS mechanoluminescent composite elastomer. Therefore, calcium fluoride is used to modify aluminate to form a high-brightness mechanoluminescent composite material. ;

[0158] Fig.10 The scatter plots of the mechanoluminescence repeatability of the mechanoluminescence composite elastomers described in Examples 7 to 10 under the same stretching conditions (stretching conditions: stretching rate 3 Hz, stretching frequency 60%) are compared. Figure 5 From the scatter plot of the force-induced luminescence repeatability of the force-induced composite elastomers described in Examples 1 to 4 and Comparative Examples 1 to 3 under the same stretching conditions, it can be seen that the repeatability of the force-induced composite elastomers described in Examples 7 to 10 is significantly better than that of the force-induced composite elastomers described in Comparative Examples 1 to 3, and with the increase of the amount of aluminum oxide used, the repeatability of the force-induced composite elastomer becomes stronger, that is, the repeatability of the force-induced composite elastomer described in Example 7 is about 10,000 times, which is 555 times that of the force-induced composite elastomer described in Comparative Example 1, 67 times that of the force-induced composite elastomer described in Comparative Example 2, and 71 times that of the force-induced composite elastomer described in Comparative Example 3, indicating that the use of calcium fluoride to modify aluminate can form a force-induced luminescence composite material with high repeatability.

[0159] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A mechanoluminescent composite material, characterized in that: The mechanoluminescent composite material comprises a metal fluoride-modified aluminate and rare earth doping ions doped in the fluoride-modified aluminate; The metal fluoride-modified aluminate comprises aluminate and metal fluoride, and a heterojunction is formed between the aluminate and the metal fluoride.

2. The mechanoluminescent composite material according to claim 1, characterized in that: The metal fluoride in the metal fluoride-modified aluminate is one or more of NaF, CaF2, MgF2, AlF3 and SrF2.

3. The mechanoluminescent composite material according to claim 1, characterized in that: The aluminate in the metal fluoride modified aluminate is M'Al2O4, SrAl4O7, Sr4Al 14 O 25 、CaAl4O7、CaAl8O 13 , CaAl 12 O 19 and Ca 12 Al 14 O 33 One or more of the following; The M' in the M'Al2O4 is one or more of Sr, Ca, Ba and Mg.

4. The mechanoluminescent composite material according to claim 1, characterized in that: The rare earth doping ion is Ce 4+ , Pr 3+ 、Eu 2+ 、Eu 3+ 、Dy 3+ , Tb 3+ 、Ho 3+ 、Sm 2+ and Tm 3+ One or more of the .

5. The mechanoluminescent composite material according to any one of claims 1 to 4, characterized in that: The molar ratio of the metal fluoride-modified aluminate to the rare earth doping ions in the mechanoluminescent composite material is 1:(0.01-0.1).

6. The method for preparing the mechanoluminescent composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing metal fluoride, Al2O3 and rare earth oxide, and sintering to obtain the mesoluminescent composite material; The metal in the metal fluoride is the metal in the metal fluoride in the metal fluoride-modified aluminate and the metal in the aluminate.

7. The preparation method according to claim 6, characterized in that: The sintering temperature is 1100-1600° C. and the sintering time is 2-5 hours.

8. The method for preparing the mechanoluminescent composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Metal carbonate, Al2O3 and rare earth oxide are mixed and first sintered to obtain MAl x O y : Ln aluminate precursor, the metal in the metal carbonate is the same as the metal in the aluminate; The MA1 x O y : a Ln aluminate precursor and a metal fluoride are mixed and subjected to a second sintering to obtain the mesoluminescent composite material, wherein the metal in the metal fluoride is the same as the metal in the metal fluoride in the metal fluoride-modified aluminate; The MA1 x O y : In the Ln aluminate precursor, M is the same type as the metal in the metal carbonate, Ln is the same type as the rare earth element in the rare earth oxide, the value range of x is 1-14, and the value range of y is 4-33.

9. The preparation method according to claim 8, characterized in that: The first sintering temperature is 1200-1700°C and the time is 2-5h; The second sintering temperature is 1100-1600° C., and the time is 2-5 hours.

10. Use of the mechanoluminescent composite material according to any one of claims 1 to 5 or the mechanoluminescent composite material prepared by the preparation method according to any one of claims 6 to 9 in mechanoluminescent composite elastomers.

Citation Information

Cited By

  • Visual mechanical luminescent ceramic, preparation method and application in grain mechanical equipment detection

    CN120172736A